2012
DOI: 10.1021/jz3011332
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Metal–Organic Precursors by Electron Bombardment in the Gas Phase for Enhanced Deposition of Solid Films

Abstract: The incorporation of gas-phase electron-impact ionization and activation of metal-organic compounds into atomic layer deposition (ALD) processes is reported as a way to enhance film growth with stable precursors. Specifically, it is shown here that gas-phase activation of methylcyclopentadienylmanganese tricarbonyl, MeCpMn(CO)3, which was accomplished by using a typical nude ion gauge employed in many ultrahigh-vacuum (UHV) studies, enhances its dissociative adsorption on silicon surfaces, affording the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…We have in the past shown the viability of this approach by using electron-impact activation of both 5 and 6 precursors for their adsorption on silicon oxide surfaces. Figure reports both XPS (left panel) ,,, and static secondary ion mass spectrometry (SSIMS; right) data from surfaces prepared using this approach to illustrate the significant gains in uptake that take place in both cases, of up to an order of magnitude in some instances, upon gas-phase activation, which was done by using the stray electrons from a nude ion gauge (hence the labeling of the tests as “ion gauge off” versus “ion gauge on”). One particularly remarkable result from this study is that a clear peak was detected in the SSIMS traces for the MeCp ligand on the surface in ex situ experiments that required mailing of the samples from the laboratory were they were prepared (Riverside, CA) to the laboratory were they were characterized (Newark, DE).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have in the past shown the viability of this approach by using electron-impact activation of both 5 and 6 precursors for their adsorption on silicon oxide surfaces. Figure reports both XPS (left panel) ,,, and static secondary ion mass spectrometry (SSIMS; right) data from surfaces prepared using this approach to illustrate the significant gains in uptake that take place in both cases, of up to an order of magnitude in some instances, upon gas-phase activation, which was done by using the stray electrons from a nude ion gauge (hence the labeling of the tests as “ion gauge off” versus “ion gauge on”). One particularly remarkable result from this study is that a clear peak was detected in the SSIMS traces for the MeCp ligand on the surface in ex situ experiments that required mailing of the samples from the laboratory were they were prepared (Riverside, CA) to the laboratory were they were characterized (Newark, DE).…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, two traces are displayed, for experiments with the chamber’s ion gauge, used for gas-phase electron-impact precursor activation, off (blue) or on (red). The left panel was adapted from ref . Copyright 2012 American Chemical Society.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of the surface was monitored using a K-type thermocouple inserted between the sample and the metallic clip that holds the sample in place. An ionization gauge is coupled to the UHV system for two purposes, to monitor the pressure of the gases during dosing and as a gas-phase electron-impact activating source for the organometallic Pt compound, as we have discussed before. , The MeCpPt­(CH 3 ) 3 precursor (purchased from Sigma-Aldrich 98% purity) was purified in situ via repeated freeze–pump–thaw cycles before introduction to the side chamber for surface dosing. This auxiliary chamber has a base pressure of 1 × 10 –8 Torr, maintained by using a turbomolecular pump.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…We have recently reported an alternative where electron excitation is carried out in the gas phase, prior to adsorption on the surface. 35 We showed that with (methylcyclopentadienyl)-Mn(I) tricarbonyl (MeCpMn(CO) 3 ) the carbonyl groups are easily removed this way, and that the remaining MeCpMn fragment is easily adsorbed and activated cleanly once adsorbed on the substrate of interest. The question remains of how general this approach may be.…”
mentioning
confidence: 99%